Calcium channel blockers and beta-blockers could increased mortality of patients with COVID-19. (14th October 2021) - Esteban-Lucia, L; Zambrano Chacon, M A; Venegas Rodriguez, A M; Devesa-Arbiol, A; Gonzalez-Rodriguez, M; Maure-Blesa, L; Avila-Barahona, P; Pello-Lazaro, A M; Gonzalez-Lorenzo, O; Kallmeyer-Mayor, A M; Fernandez-Roblas, R; Villar-Alvarez, F; et al.
Abstract: Background: High incidence of cardiovascular events has been described among patients with COVID-19 and since the beginning of the pandemic concerns have been expressed with medical treatments for cardiovascular disease, as they could contribute to the severity of illness in patients with COVID-19. We aim to analyze the effect of chronic treatment with calcium channel blockers and beta-blockers on COVID 19 severity in a Spanish cohort during the 2020 pandemic. Methods: Observational study including all consecutive patients (≥40 years old) diagnosed with SARS-CoV-2 through PCR in the microbiology laboratory of our hospital, from March 2nd to 20th 2020. Clinical characteristics and drugs were recorded. The Primary end-point (PE) was all-cause death and the secondary end-point (SE) was the combined of death or the need for orotracheal intubation until 30 days of infection symptoms onset. Results: We included 704 patients in our study. Baseline characteristics of the overall cohort can be seen in the table. Median age was 61 years old (IQR 52.9–72.9); 52.7% were female. 34.7% and 12.6% had hypertension and diabetes respectively. After a median follow-up of 111.5 days, 58 patients (8.2%) needed orotracheal intubation and 133 patients (18.9%) died. Secondary endpoint (all-cause death or need for orotracheal intubation) was reached by 164 patients (23.3%). The table described clinical differences between survivors and deceased patients. After multivariate Cox modeling, age, male gender, diabetes, previous lung disease, BMI and the chronic intake of calcium channel blockers (HR 1.74, 95% CI (1.11–2.75), p=0.016) and beta-blockers (HR 1.71, 95% CI (1.07–2.76), p=0.026) were independently related with mortality. Other cardiovascular drugs (Antiplatelets, anticoagulants, diuretics, mineralcorticoid-receptor antagonists, angiotensin-receptor blockers, angiotensin-converting enzyme inhibitors and statins) did not influence survival after SARS-CoV 2 infection (Figure). The secondary outcome was reached by 164 patients (23.3%) and chronic treatment with calcium channel blockers remains as an independent predictor of mortality (HR 1.55, 95% CI (1.01–2.37), p=0.044). Conclusions: Chronic treatment with calcium channel blockers and beta-blockers are independent predictors of mortality after SARS-CoV-2 infection. Further studies are needed to confirm these results. Funding Acknowledgement: Type of funding sources: None.